T-Cell Leukemia Characteristics, Treatment and Prevention - Tomita, Mariko (IntechOpen, 2013)
T-cell leukemia is relatively rare malignancy of thymocytes. There are around 20 entities and variants of this disease. Each of them has different characteristics, including pathogenesis, epidemiology, diagnosis, therapeutic approaches, and prognosis. Although T-cell leukemia is relatively rare malignancy, many types of T-cell leukemias still have a very poor prognosis due to rapid progression. Therefore, the development of novel therapeutic and preventive strategies is necessary to improve prognosis. The purpose of this book is to provide a comprehensive overview of the disease from the basics of pathogenesis, epidemiology, morphology, and immunological features. This book also highlights the most recent achievements from basic and clinical researches including molecular mechanisms and novel therapies of T-cell leukemia.